Oesophageal inflammation and tumourigenesis - inherited variation in an Irish population - Babar, Mahwash M. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2010)
Cancer is a major medical challenge of this era and early diagnosis of cancer is critical to curative therapy. The search for biomarkers that may indicate the risk or presence of cancer is ongoing in thousands of laboratories around the world. Individual variability of DNA sequence distinguishes one person from another and have been used to search for biomarkers for cancer susceptibility.
Keywords: Genomic and Clinical Surgery Research Group, M.D.; M.D. Trinity College Dublin